2009
DOI: 10.1007/s00595-008-3974-5
|View full text |Cite
|
Sign up to set email alerts
|

A new hydrocolloid dressing prevents surgical site infection of median sternotomy wounds

Abstract: The new hydrocolloid dressing, applied with an occlusive dressing technique to median sternotomy wounds, prevented SSI and was cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Various studies have focused on techniques or devices to reduce SWI such as microbial sealant prior to surgery [ 14 ], different methods of sternal closure (Robicsek technique [ 15 ], rigid-plate sternal fixation [ 16 ], nitinol clips [ 17 ]), different methods of skin closure (intradermic closure [ 18 ], skin staples [ 19 ], liquid skin adhesive [ 20 ], prophylactic gentamycin-collagen sponge [ 21 ], topical application of autologous blood products [ 22 ], hydrocolloids [ 23 ], growth factors [ 24 ]) or a combination of them. All these techniques have showed good results reducing incidence of mediastinitis and reducing the length of stay in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have focused on techniques or devices to reduce SWI such as microbial sealant prior to surgery [ 14 ], different methods of sternal closure (Robicsek technique [ 15 ], rigid-plate sternal fixation [ 16 ], nitinol clips [ 17 ]), different methods of skin closure (intradermic closure [ 18 ], skin staples [ 19 ], liquid skin adhesive [ 20 ], prophylactic gentamycin-collagen sponge [ 21 ], topical application of autologous blood products [ 22 ], hydrocolloids [ 23 ], growth factors [ 24 ]) or a combination of them. All these techniques have showed good results reducing incidence of mediastinitis and reducing the length of stay in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…When a tight hydrocolloid dressing applied on the wound for 7 days was used, a significant difference with regard to incidence of superficial and deep infections was found as compared to patients treated with Tegaderm dressings changes in the postoperative period (6). No differences were found as compared to wounds sutured with cutaneous sutures and closed with staples with regard to incidence of wound infections, but total complications (erythema, effusion, necrosis, infection) were more common in the group of wounds managed with staples (7).…”
mentioning
confidence: 99%
“…Teshima et al found the hydrocolloid dressing to play an important role in the prevention of superficial infections, reporting 3.4% of infections. 14 In comparison, the use of traditional gauzes is associated with lower rates of both deep and superficial complications, maybe because it imposes more frequent dressing changes, as the drainage is visible through the transparency of the gauze. As shown in another article comparing NPWT and dry dressing, deep infections rate was 0 versus 11.1%, 15 that supports our results.…”
Section: Discussionmentioning
confidence: 99%